Tinjauan Form Risk Assessment di Area Packaging Departemen Cold Cutting PT. X - Fahrezi, Ahmad; Herwanto, Dene (Fakultas Teknik Universitas Tulang Bawang, 2025)
Occupational Safety and Health (OHS) is an important element in the industry to ensure safe and healthy working conditions for workers. PT. X implements OHS through the use of risk assessment forms, especially in the packaging area of ​​the Cold Cutting department. The purpose of this study is to evaluate the risk assessment form used by the company and adjust it to the Job Safety Analysis (JSA) method. The results of the evaluation indicate that the risk assessment form used by the company is not fully detailed in identifying the risks in each job, compared to the JSA method. Therefore, it is recommended that the company adopt a more general and standardized JSA format to improve clarity and understanding, especially for parties outside the company. The implementation of this proposal is expected to improve the effectiveness of risk management and occupational safety, while reducing the potential for accidents in the workplace, thereby increasing the company's overall productivity and operational efficiency. Keywords: Job Safety Analysis (JSA), K3, Risk Assessment